(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
The correlation between COVID-19 and educational services in Cross River State has been examined. The COVID-19 pandemic has been recorded in all countries of the world with significant adverse consequences on education. Specifically, COVID-19 is examined regarding school closures and educational disruptions, exacerbation of disparities in learning outcomes, increased school dropouts, and the ripple effect beyond the COVID-19 pandemic. The consequence has been missed education opportunities for most students, especially those in rural communities of Sub-Saharan Africa. The paper is descriptive and qualitative. Literature is obtained from secondary sources and examined through content analysis. Education should be stimulated by financially supporting school-related expenses for children whose families suffered economic hardship because of this disruption caused by the pandemic. Governments may need to provide remedial education for students who suffered due to the inability to functionally access online education. The government should check incidents of increased school drop-outs by subsidizing school materials as a means of moderating the losses experienced by all categories of learners.